Comparison of Performance Characteristics of LPG and Gasoline - Fuelled Single Cylinder SI Engine - Saad Abdul Qadir Abdul Azeez (Tikrit Journal of Engineering Sciences, 2016)
The investigations have been concentrated on decreasing fuel consumption by using alternative fuels and on lowering the concentration of toxic components in combustion products. LPG as an alternative to gasoline has emerged as a solution to the deteriorating urban air quality problem, especially in an oil country like Iraq. LPG has already been used as cooking fuel in Iraq. In the present paper practical tests of various operating parameters and concerns have been prepared for better understanding of operating conditions and constrains for a LPG fueled internal combustion engine. The results show that HUCR for gasoline was 8:1, and for LPG was 10:1. bsfc reduced by using LPG at its HUCR, while at CR=8:1 it became higher than that for gasoline. Volumetric efficiency reduced by using LPG due to its gaseous nature, but it was improved when the engine was run at HUCR. Brake thermal efficiency depends on bsfc and bp, so LPG preceded gasoline at medium speeds and torques. Exhaust gas temperatures reduced by using LPG, the minimum values were when the engine operated at CR= 8:1. The maximum values were for gasoline share.